An Interpretative Phenomenological Analysis Study On Customer Lived Experiences Of Emotionally Intelligent Service Agents - Isma Azis Riu (International Journal of Education Management and Religion, 2026)
This study aims to examine how the emotional intelligence of customer service agents influences problem resolution, customer satisfaction, and repurchase intention within Platform X, a major ride-hailing and food-delivery service in Indonesia. As customers increasingly encounter service failures such as delayed refunds, repeated driver cancellations with charges applied, and double payment incidents, understanding how they experience emotionally intelligent responses becomes essential. This research employs a qualitative approach using Interpretative Phenomenological Analysis (IPA) to explore customers’ meaning-making processes during emotionally charged interactions. The population of this study consists of active users of Platform X. A homogeneous purposive sample of six participants aged 20–35 years was selected based on their experience with at least one of the identified service failures and direct communication with a human service agent. Data were collected through semi-structured in-depth interviews as the primary instrument, complemented by field notes. All interviews were conducted online and audio-recorded with participant consent. The results reveal three key themes: experiencing emotional understanding and recognition, interpreting the agent’s intentions during the resolution process, and forming emotional and relational outcomes that shape satisfaction and repurchase intention. These findings demonstrate that emotionally intelligent service behaviours help restore trust, reduce emotional distress, and strengthen long-term customer loyalty.